2015
DOI: 10.1501/vetfak_0000002655
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effect of montelukast sodium against hepatic radioiodine (131I) toxicity: A histopathological investigation in the rat model

Abstract: Summary: Radioactive iodine (131 I) is a known radionuclide which is used both for diagnostic and therapeutic purposes in the treatment of hyperthyroidism and thyroid cancer. Montelukast sodium (Cysteinyl leukotriene receptor-1 antagonist) is also a wellknown antioxidant drug. This study aimed to evaluate the histopathological changes in rat livers at the third month following 131 I treatment and the radioprotective effect of Montelukast sodium (ML) against 131 I-related liver damage. Thirty female Wistar Albi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similarly, intraperitoneal melatonin treatment decreased the tissue advanced the oxidation of protein products and malondialdehyde levels and increase the total sulfhydryl level as well as reducing the early histopathologic damage of the liver after RAIT [34]. Moreover, montelukast had a partial radioprotector effect against the long-term liver damage at the third month of RAIT, particularly in terms of hyperemia and capsule thickening [10]. In the current study, RAIT enhanced oxidative stress in liver tissue by causing an increase in oxidant tissue malondialdehyde levels and a decrease in antioxidant total sulfhydryl levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, intraperitoneal melatonin treatment decreased the tissue advanced the oxidation of protein products and malondialdehyde levels and increase the total sulfhydryl level as well as reducing the early histopathologic damage of the liver after RAIT [34]. Moreover, montelukast had a partial radioprotector effect against the long-term liver damage at the third month of RAIT, particularly in terms of hyperemia and capsule thickening [10]. In the current study, RAIT enhanced oxidative stress in liver tissue by causing an increase in oxidant tissue malondialdehyde levels and a decrease in antioxidant total sulfhydryl levels.…”
Section: Discussionmentioning
confidence: 99%
“…Vasil'ev et al [8] obtained a moderate decrease in absorptive and secretory hepatocyte function associated with both hypothyroidism and radiation factor in thyroid cancer patients received RAIT. In animal studies, it has been shown that RAIT caused significant morphological damage to rat livers in both short and long-term period of treatment [9,10]. It has been observed that the high dose RAI ablation therapy as 75-150 mCi might lead to drug-induced liver injury (DILI) in the thyroidectomized patient [11].…”
Section: Introductionmentioning
confidence: 99%